Vegetable twig causing obstructive parotid sialadenitis - Jonathan Theodore Gondi; Suhasini Gazula (Wolters Kluwer Medknow Publications, 2016)
We report the case of a 4-year-old boy with obstructive parotid sialadenitis in whom the classic clinical presentation clinched the diagnosis which highlights the importance of applied anatomy and clinical examination even in the present age of novel imaging techniques.